RBTT-07. A PHASE 2 TRIAL OF PEMBROLIZUMAB AND BEVACIZUMAB IN MELANOMA BRAIN MET PATIENTS. (11th November 2019) - Kluger, Harriet M; Forsyth, Peter; Khushalani, Nikhil; Eroglu, Zeynep; Sznol, Mario; Tran, Thuy; Jilaveanu, Lucia; Cohen, Justine V; Hegde, Upendra; Wei, Wei; Mahajan, Amit; Goldberg, Sarah B; et al.
Abstract: BACKGROUND: Pembro monotherapy (NCT02085070) produces responses in 26% of (mel) BrM pts. VEGF inhibitors (VEGFi) enhance anti-PD-1 activity in preclinicals. Therefore, we initiated a phase 2 study (NCT02681549) of pembro plus bev in BrM pts. METHODS: Eligibility includes advanced mel, > 1 asymptomatic BrM, diameter 5-20mm, no steroids, no prior PD-1/PD-L1 or VEGFi. Pembro IV 200mg q3 wks for < yrs with bev 7.5mg/kg for the first 4 cycles. Primary endpoint was BrM RR by modified RECIST. RESULTS: Between 8/2016 - 1/2019, 20 mel pts were enrolled. 60% were male mdn age 62;ECOG PS was 0 in 16 and 1 in 4 pts; LDH > ULN in 20%; 4 (20%); 10 were BRAFmt; 8 pts (40%) had > 4 untreated BrM. 12 had a BrM response (7 CR, 5 PR); 1 each with SD, unevaluable and an unconfirmed PR, for an ORR BrM of 60% (12/20). All responses lasted 7+ to 30+ mths. 16 pts are alive. AEs attributable to bev include hypertension, microscopic diverticular perforation and wound dehiscence (1 pt each, all resolved). 1 had mucositis attributed to Pembro. Three d/c'd treatment for grade 3 ALT elevation. Cerebral edema decreased in all pts with baseline edema. CONCLUSIONS: Pembro plus bev demonstrates promising activity in melanoma BrMs compared to pembro alone. The pre-specified primary endpoint (> 4 BrM responses/20) was met, supporting further study. The toxicity profile was similar to pembro alone.